Evaluasi kapasitas masyarakat tangguh bencana di kawasan rawan erupsi gunung api merapi - Fahmi, Wikan Amarudin; Hizbaron, Dyah Rahmawati (Jurnal Teknosains, 2023)
Disaster events have become a national issue, one of the reasons is that Indonesia is crossed by a series of volcanoes, such as Merapi Volcano. It erupted back in 2010 and caused massive impact, especially at Kepuharjo Village, Sleman Regency, Yogyakarta. This research is intended to identify the capacity of community resilience due to the Merapi Volcano eruption at Desa Kepuharjo, Kabupaten Sleman. The study collects primary data from interviews and questionnaires from unit samples of Kepuharjo Village using simple random sampling techniques. The data collected from the modified version of the questionnaire were processed using scoring techniques and analyzed using descriptive frequency. The research revealed that the questionaire to capture capacity that generally employed are not fully compliant to be used at the research area. Overall, the questionaire able to capture to assess the capacity classification which are medium (the capacity achievement is comprehensive but not significant to reduce the impact of the disaster) and high ((the capacity achievement is comprehensive and there is a commitment between the government and the community). Kepuharjo Village is classified into classes of 3-5 with a percentage of 65%. Efforts to increase capacity have been carried out by the government, assisted by the community, both by establishing institutions, physical mitigation, and non-physical mitigation.